2022
DOI: 10.1249/jsr.0000000000001002
|View full text |Cite
|
Sign up to set email alerts
|

Sports Medicine Health Care Access in Michigan High Schools: Access to Athletic Trainers

Abstract: Reduced access to health care leads to health disparities across the United States. Adolescents use the health care system infrequently. The presence of an athletic trainer in high schools increases access to health care in student-athletes. Many Michigan high schools do not provide athletic trainer services for their student athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The limitations of this study are the lower response rate, possible bias in survey responses, and generalizability limited to Illinois public high schools of the type in the study. However, our results are consistent with the results of other studies, including a recent study of disparities in access to ATs in Michigan high schools (12).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The limitations of this study are the lower response rate, possible bias in survey responses, and generalizability limited to Illinois public high schools of the type in the study. However, our results are consistent with the results of other studies, including a recent study of disparities in access to ATs in Michigan high schools (12).…”
Section: Discussionsupporting
confidence: 93%
“…Although Illinois state law requires all school athletic facilities to have at least one AED, a single AED is usually inadequate. Previous studies have identified socioeconomic disparities in access to an AT (10)(11)(12), as well as racial and socioeconomic disparities in access to AEDs (13).…”
Section: Introductionmentioning
confidence: 99%